The inhibition performance in relation to the adsorption of a polymeric kinetic inhibitor towards THF hydrates in the presence of methanol, ethanol and monoethylene glycol - Foo, C.; Ruan, L.; Lou, Xia (Elsevier Inc., 2016)
This report details an investigation of the adsorbability and inhibition performance of a kinetic inhibitor (KHI), namely poly(ethyleneoxide-co-vinylcaprolactam) (PEO-co-VCap-1), in relation to tetrahydrofuran (THF) hydrates in the presence of low concentrations of methanol, ethanol and monoethylene glycol during the hydrates formation process. Results from the quantitative examinations indicate that the presence of these molecules increases KHI adsorption onto the hydrate crystals and reduces the cage occupancy of THF. Improved inhibition performance of KHI by the added chemicals upon THF hydrates formation was well demonstrated in all cases. The inhibition performance was strongly correlated to the KHI adsorbability, irrespective of the type and/or concentration of the chemical additives.